Geographical, Socioeconomic, and Gender Inequalities in Opioid Use in Catalonia - Sara Serra-Pujadas; Cristina Alonso-Buxadé; Júlia Serra-Colomer; Júlia Folguera; Neus Carrilero; Anna García-Altés; Anna García-Altés; Anna García-Altés (Frontiers Media S.A., 2021)
Background: In recent years, worldwide opioid use has seen a sharp increase, especially for the treatment of chronic non-cancer pain. Catalonia is no exception to this trend. However, no recent studies have addressed the socioeconomic and gender inequalities in opioid use in the different geographical areas of Catalonia.Methods: We performed an ecological study to analyse the associations between socioeconomic status, gender and the use of opioids in the 372 Health Areas of Catalonia. Robust Poisson models were performed to analyse the data provided from the Central Register of Insured Persons and dispensing data from the Electronic Prescription Database.Results: The results show that socioeconomic status has a major impact on opioid use, with the most deprived areas presenting the highest levels of use. There are major inequalities in the DDD/1,000 inhabitants per areas. Moreover, women have much higher utilization rates than men, especially in more deprived areas. The greatest difference is observed in the use of weak opioids in women: the DDD/1,000 inhabitants per day was 2.34 in the area with the lowest use, compared with 22.18 in the area with the highest use.Conclusions: Our findings suggest that stronger action is needed to promote best practices in prescribing for chronic pain and to reduce socioeconomic and gender variation between geographical areas. This study provides a model for routine monitoring of opioid prescription for targeted interventions aimed at lowering high-dose consumption in specifically identified areas.